2022
DOI: 10.1371/journal.pone.0263080
|View full text |Cite
|
Sign up to set email alerts
|

Repeated glucose spikes and insulin resistance synergistically deteriorate endothelial function and bardoxolone methyl ameliorates endothelial dysfunction

Abstract: Background Both insulin resistance and postprandial glucose spikes are known for their potential to induce vascular endothelial dysfunction in individuals with metabolic syndrome. However, these factors are inextricable, and therefore, their relative contributions to inducing endothelial dysfunction remain elusive. In this study, we aimed to disentangle the effects of these factors and clarify whether bardoxolone methyl (CDDO-Me), a novel nuclear factor erythroid 2-related factor 2 (Nrf2) activator, protects a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…In this study, the high‐fat diet group exhibited a significant increase in ROS production, attenuated endothelial‐dependent vasodilation under increasing concentrations of FFA and SOD ameliorated the FFA induced endothelial dysfunction. On the other hand, a previous study that examined endothelial function with a similar experimental system showed increasing oxidative stress and aortic endothelial dysfunction under hyperglycemic conditions in diet‐induced obesity and insulin resistance model rats 19 . In the study, an antioxidant protected the aortic endothelial function as in our study.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…In this study, the high‐fat diet group exhibited a significant increase in ROS production, attenuated endothelial‐dependent vasodilation under increasing concentrations of FFA and SOD ameliorated the FFA induced endothelial dysfunction. On the other hand, a previous study that examined endothelial function with a similar experimental system showed increasing oxidative stress and aortic endothelial dysfunction under hyperglycemic conditions in diet‐induced obesity and insulin resistance model rats 19 . In the study, an antioxidant protected the aortic endothelial function as in our study.…”
Section: Discussionmentioning
confidence: 82%
“…NF‐E2‐related factor 2 (Nrf2), a major transcription regulator that activates antioxidants, including SOD2, and anti‐inflammatory and cell protective gene expression, may be another factor that increases the expression of SOD2 in the thoracic aorta with luseogliflozin administration. It has been reported that activating Nrf2 by bardoxolone methyl increased SOD2 gene expression 19 . Furthermore, SGLT2 inhibitors could increase Nrf2 expression in both diabetic and non‐diabetic animal models 33 , 34 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…9,10 Microvascular diseases cause damage to smaller blood vessels and can lead to complications such as nephropathy, retinopathy, neuropathy and vascular abnormalities in lower extremities. 11,12 Because the endothelial cells of the microvasculature are insulin independent, 13,14 these tissues constantly receive unregulated glucose input. This increases the prevalence of these complications.…”
mentioning
confidence: 99%